Experimental realisation of near-equilibrium adverse-pressure-gradient turbulent boundary layers - Vila, C. Sanmiguel; Vinuesa, Ricardo; Discetti, Stefano; Ianiro, Andrea; Schlatter, Philipp; Orlu, R. (Experimental Thermal and Fluid Science, 2020)
A new experimental database of adverse-pressure-gradient (APG) turbulent boundary layers (TBLs) obtained through hot-wire anemometry and oil-film interferometry covering a momentum–loss Reynolds number 450<Reθ<23450 and Clauser pressure-gradient-parameter range up to β≈2.4 is presented. Both increasing and approximately constant β distributions with the same upstream history are characterised. Turbulence statistics are compared among the different pressure-gradient distributions with additional numerical and experimental zero-pressure-gradient (ZPG) TBL data. Cases at approximately constant β, which can be considered as canonical representations of the boundary layer under a certain pressure-gradient magnitude, exhibit skin-friction and shape-factor curves consistent with the ones proposed by Vinuesa et al. (2017). These curves show a similar scaling behaviour as those proposed by Nagib et al. (2007) for ZPG TBLs. The pre-multiplied power-spectral density is employed to study the differences in the large-scale energy content throughout the boundary layer. Two different large-scale phenomena are identified, the first one related to the pressure gradient and the second one (also present in high-Re ZPG TBLs) due to the Reynolds number. Recently proposed scaling laws by Kitsios et al. (2016) and Maciel et al. (2018) are tested over a wider Reynolds-number range and for different β cases. The mean velocity and streamwise velocity fluctuation profiles are found to be dependent on the upstream development. The mean velocity profile is found to be self-similar only in the outer region, in agreement with classical theory. The mean and higher-order statistics of the new APG TBL database are made available under www.flow.kth.se.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Pressure gradient flows; Turbulent boundary layer; Turbulent flows